The Influence of the Work Environment and Financial Compensation on the Performance of Employees of SMA Negri 1 Karangbinangun Lamongan - Sugeng Pramono; Didik Puji Wahyono; Muhammad David (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to determine the effect of the work environment and financial compensation on the performance of educators at SMA Negeri 1 Karangbinangun. The study uses a quantitative method. The population in this study consists of all 59 educators at SMA Negeri 1 Karangbinangun, who are also used as the sample with a total sampling method. The variables studied are the work environment and financial compensation as independent variables, and educator performance as the dependent variable. The data were analyzed using multiple linear regression analysis with SPSS version 25. The results of this study indicate that the work environment variable has a positive and significant effect on employee performance, financial compensation has a positive and significant effect on employee performance, and simultaneously, both the work environment and financial compensation have a positive and significant effect on employee performance.